Lasers in Orthopedic, Dental, and Veterinary Medicine II 1993
DOI: 10.1117/12.148317
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced autofluorescence of caries

Abstract: The laser induced autofluorescence from carious regions of human teeth was studied using a krypton ion laser at 407 flirt as excitation source, a fiberoptical detection system combined with a polychromator and an optical muLtichannel analyzer. In addition, time.resolved and time-gated fluorescence measurements in the nanosecond range were carried out. It was found that carious regions contain different fluorophores which emit in the red spectral range. The emission spectra with maxima around 590 nm, 625 nm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 3 publications
3
93
0
10
Order By: Relevance
“…13 In another study, Lennon et al compared FACE with CME and found that FACE left less bacterially infected dentine after excavation than CME. 35 They concluded that FACE is more effective at removing infected dentine without significantly increasing cavity size when compared to CE. The relative cavity volume (MIP) of FACE in their study was 3, which is similar to our result of 3.19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In another study, Lennon et al compared FACE with CME and found that FACE left less bacterially infected dentine after excavation than CME. 35 They concluded that FACE is more effective at removing infected dentine without significantly increasing cavity size when compared to CE. The relative cavity volume (MIP) of FACE in their study was 3, which is similar to our result of 3.19.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have used histology to characterize the bacteria left after caries excavation using the FACE technology. 18 After application of the FACE method to excavate caries, teeth sections were evaluated for the presence of bacteria in the dentin tubules using light microscopy 19,35 or laser-scanning confocal microscopy. 18,20 Those studies confirmed that the FACE method removes more caries-affected tissue than CE or caries dye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The porphyrin molecules are also endogenic phosphors, the content of which in cells considerably increases under some pathologic conditions. Besides, some bacteria, causing, e.g., the inflammation diseases of skin [239] and gums [240], inhabiting the caries tooth lesions [241], can accumulate considerable amounts of porphyrins. Combining the measured autofluorescence spectra with those of reflection and absorption, OCT and other optical methods allows the diagnostics of caries and tooth tissue demineralisation [241][242][243][244][245], skin cancer [246,247], and pre-cancer changes of cervical tissue [248], mammary gland [249], and other diseases.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…O tecido dentário saudável não apresenta bandas de emissão no vermelho, assim, somente o tecido cariado irá fluorescer. Os espectros de excitação e emissão das lesões de cárie são típicos de porfirinas, principalmente da protoporfirina IX, a possível fonte de porfirina no tecido cariado é a biossíntese bacteriana que ocorre no local (KONIG et al, 1998). HAMISHAKI et al (2014) realizaram um estudo comparativo entre a inspeção visual realizada por dentistas com experiência clínica e um aparelho de fluorescência a laser (DIAGNOdent®) para diagnosticar a cárie dentária secundária.…”
Section: Odontologiaunclassified